Influence of crystalline phase transformation induced by airborne-particle abrasion and low-temperature degradation on mechanical properties of dental zirconia ceramics stabilized with over 5 mol% yttria. (January 2022) - Nakamura, Keisuke; Tarkeshi, Aria; Niklasson, Alexander; Shishido, Shunichi; Svanborg, Per; Barkarmo, Sargon; Örtengren, Ulf
Abstract: Monolithic dental prostheses fabricated from 5 mol% yttria-stabilized zirconia (5YZ) have been developed to improve the translucency of conventional 3 mol% yttria-stabilized zirconia. In this study, we aimed to evaluate the influence of airborne-particle abrasion (APA) and low-temperature degradation (LTD) on the mechanical properties of 5YZ in association with the crystalline phase transformation. In total, 120 disc-shaped specimens of two brands of 5YZ (Lava Esthetic and Katana UTML) were prepared. The specimens were divided into four groups (n = 15 for each group): (i) control, (ii) APA, (iii) LTD, and (iv) APA + LTD groups. APA was performed with 50 μm alumina particles, and LTD was induced by autoclaving at 134 °C for 50 h. The biaxial flexural strength of the specimens was assessed using a piston-on-three-ball test according to ISO 6872:2015, and Vickers hardness was determined using a microhardness tester. The crystalline phase was analyzed by the Rietveld refinement of X-ray diffraction patterns. APA significantly increased the flexural strength of the Lava Esthetic specimens, whereas LTD hardly affected the strength of both materials. APA and APA + LTD significantly increased the Vickers hardness of both materials. According to Rietveld analysis, the pseudocubic phase was predominant in both materials, i.e., 66 mass% and 81 mass% in the Lava Esthetic and Katana UTML specimens, respectively. APA induced the rhombohedral phase at approximately 37 mass% in both materials, while LTD induced the monoclinic phase at 2.8 mass% in the Lava Esthetic specimens and 0.9 mass% in the Katana UTML specimens. APA + LTD weakly affected the amount of the rhombohedral phase but slightly increased the amount of the monoclinic phase. These findings suggest that APA may improve the mechanical properties of 5YZ, particularly hardness, via the generation of the rhombohedral phase. In contrast, the influence of LTD on the mechanical and microstructural properties of 5YZ was limited. Graphical abstract: Image 1 Highlights: We tested properties of two dental zirconia products stabilized with >5 mol% yttria. Pseudocubic phase was predominant in both materials. Airborne-particle abrasion (APA) and low-temperature degradation (LTD) were applied. APA and APA + LTD significantly increased Vickers hardness of both materials. APA and APA + LTD induced the rhombohedral phase at about mass 37% in both materials.